2021
DOI: 10.1111/apt.16257
|View full text |Cite
|
Sign up to set email alerts
|

Letter: proton pump inhibitor use and bone fracture risk—a mechanistic point of view. Authors' reply

Abstract: LINKED CONTENTThis article is linked to Labenz et al and Sugiyama papers. To view these articles, visit https://doi.org/10.1111/apt.16008 and https://doi.org/10.1111/apt.16231

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The effect of PPIs on fracture in patients with cirrhosis may be multifactorial, since PPIs may increase the risk of falls by triggering mild HE and converting it to overt hepatic encephalopathy (OHE), which in turn increases the risk of fracture. However, the authors were unable to adjust for this factor 118 . Therefore, the effect of PPIs on fracture risk in patients with cirrhosis remains to be clarified.…”
Section: Ppi and Cirrhosismentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of PPIs on fracture in patients with cirrhosis may be multifactorial, since PPIs may increase the risk of falls by triggering mild HE and converting it to overt hepatic encephalopathy (OHE), which in turn increases the risk of fracture. However, the authors were unable to adjust for this factor 118 . Therefore, the effect of PPIs on fracture risk in patients with cirrhosis remains to be clarified.…”
Section: Ppi and Cirrhosismentioning
confidence: 99%
“…In a population-based study, PPIs were found to be associated with an increased risk of bone fracture in cirrhotic patients (OR 1.34, 95% CI 1.20-1.51), indicating that such association was dose-dependent and most significant in patients under 70 years old and in men. 116 Sugiyama 118 has noted that this may be a mechanistic view resulting from the retrospective study design as PPIs have a slight effect on the risk of falls and no effect on bone mineral density and structure, which are associated with a risk of fracture in cirrhotic patients. 117 The effect of PPIs on fracture in patients with cirrhosis may be multifactorial, since PPIs may increase the risk of falls by triggering mild HE and converting it to overt hepatic encephalopathy (OHE), which in turn increases the risk of fracture.…”
Section: Ppis and Extra-gastrointestinal Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation